(untitled) (Journal of Global Arts Studies, 2024)
Background: A large number of “animal style” metal ornaments have been unearthed from the aristocratic cemetery of the Xirong in Majiayuan, Gansu Province. The imagery style of these artistic ornaments bears a strong influence of Eurasian Steppe culture, holding significant importance for the study of the prehistoric Silk Road and ancient cultural exchanges between the East and West. Objective: This study aims to explore the gold ornaments of animal style in the Majiayuan cemetery, focusing on analyzing their cultural and artistic value. Through the study of images, it seeks to reveal cultural exchanges and artistic integration across prehistoric Eurasia. Methods: The study employs image analysis and comparison with historical literature to classify and analyze the animal-style decorative items in the Majiayuan cemetery, particularly focusing on the depiction of large-horned sheep and solitary predators in animal bite plaques and chariot decorations, to explore their stylistic features and cultural value. Results: The results indicate that the animal-style metal ornaments in the Majiayuan Cemetery exhibit unique artistic forms and techniques, closely associated with the influence of Scythian nomadic culture, especially that of the Pazyryk culture. Conclusion: The study demonstrates that the Majiayuan cemetery reveals an early nomadic luxurious and stunning artistic style and inclusive cultural traits formed through the strong collision and integration of the Xirong people with exotic cultures. It explains the close cultural exchanges between the northern regions of China and Eurasian steppe nomadic peoples in prehistory.